Trends in Persian medicinal terminology a progressing field of interdisciplinary research - Naseri, Mohammad Hasan; Hesami -Tackallou, Saeed; Ghanbari, Atefeh; Dalilan, Sona (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Conceptualization for new findings is the main aim of science and technology development. Sometimes new concepts are pathfinders for science and starting fundamental revolutions in science. An important area in scientology or scientific studies is the concept and term field, so terminology and its effect on science and technology is one of the most important subjects in the last decade. Standardization in scientific terms (scientific term selection) is one of the strongest terminology methods. These methods break down the terms to their meaningful parts or use prevalent terms, which are common among people or use eponyms and abbreviation processes, and finds the appropriate equivalent for them. The word parts are prefixes, suffixes and stems. In medical sciences, terms are mostly originated from Latin stems, so this method could be extremely efficient in these fields. The terminology committee of Persian Academy studied the highly frequent prefixes, suffixes and stems to help the standardization of terminology in medical sciences. This research introduces methods of term selection, some approved terms and their Persian equivalents. Term selection for medical terms is not an obligatory rule, but is a proposal for meeting the researchers need to strength Persian language as a scientific language.